2008
DOI: 10.3201/eid1408.080221
|View full text |Cite
|
Sign up to set email alerts
|

Puumala Hantavirus Excretion Kinetics in Bank Voles (Myodes glareolus)

Abstract: One-sentence summary for table of contents: Virus may be transmitted by saliva, urine, and feces, and saliva may play a role in transmission to humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
110
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 20 publications
4
110
0
1
Order By: Relevance
“…The hantavirus infections in these rodents were probably produced through inhalation of viral particles or licking. Hardestam et al 45 observed that hantavirus transmission through saliva among rodents is more common than through inhalation of excreta containing viral particles.…”
Section: Discussionmentioning
confidence: 99%
“…The hantavirus infections in these rodents were probably produced through inhalation of viral particles or licking. Hardestam et al 45 observed that hantavirus transmission through saliva among rodents is more common than through inhalation of excreta containing viral particles.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with this virus is considered to be chronic (Meyer and Schmaljohn, 2000). Voles experience a transient period of viremia, beginning a few days after infection and peaking 2-4 weeks post-infection (Hardestam et al, 2008), although viral RNA has been detecting 84 days post-infection in some experimentally infected bank voles. Periodic episodes of viral recrudescence may occur during the lifetime of the vole, because of changes in the virus and/or host immune response (Hardestam et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Voles experience a transient period of viremia, beginning a few days after infection and peaking 2-4 weeks post-infection (Hardestam et al, 2008), although viral RNA has been detecting 84 days post-infection in some experimentally infected bank voles. Periodic episodes of viral recrudescence may occur during the lifetime of the vole, because of changes in the virus and/or host immune response (Hardestam et al, 2008). Besides, anti-hantavirus immunoglobulin G are usually detectable 2 weeks after infection and seems to remain detectable for the lifetime of the rodents (see references in Easterbrook and Klein, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main host of PUUV is the bank vole (Myodes glareolus), and the virus is predominantly transmitted horizontally to humans via exposure to contaminated vole excreta [13,39,42]. Human infection is characterized by sudden onset of fever, head and backache, vomiting, and abdominal pain often accompanied by visual disturbances [24].…”
Section: Introductionmentioning
confidence: 99%